A Late Middle Kingdom Private Stela of the Priests of Hathor (Cairo Museum CG 20780) - El Gabry, Dina.
In this paper, the stela of Senbi (CG 20780), the great wab-priest of Hathor, as well as overseer of fields, and his wife Nebunakht, who was also a priestess of Hathor, is published exclusively for the first time. The stela is currently preserved in the Egyptian Museum in Cairo. Unfortunately, nothing is mentioned about this stela’s provenance in the museum’s records. The stela alludes to several titles of both Senbi (imy-r3 3?(w)t and w‘b ‘3 n ?wt-?r) and his wife Nebunakht (?mt n?r ?wt-?r), but the unique peculiarity of the stela is its reference to the epithet sn ?q3 “The Brother of the Ruler.” This stela can be dated to the late Middle Kingdom based on the individuals’ names, as well as the titles of the owner and his family. The design and the depiction of multiple members in the stela are also characteristics of the Middle Kingdom stelae. All these criteria, along with some relevant grammatical features contribute to a late Middle Kingdom date—most likely the Thirteenth Dynasty. The author describes the stela, discusses its philological, iconographical, and stylistic features, and examines the titles of its owners.